Impact of Storage Bag Location on Performance in a Manual Wheelchair Agility Test - Monteiro, Reverson Tadeu [UNESP]; da Silva Santana Castro, Carla; Medola, Fausto Orsi [UNESP] (Springer Nature, 2025)
Individuals with physical disabilities often rely on manual wheelchairs for autonomous mobility, where device configuration and weight distribution critically influence propulsion performance. This study investigated the effect of adding a 5-kg storage bag at different positions on a manual wheelchair during an agility test simulating real-life maneuvers. Twenty able-bodied participants, with no prior wheelchair experience, completed a timed course under four conditions: without added weight, and with the bag attached at the front of the seat, behind the backrest, and on the rear wheel spokes. Results showed that adding weight on the rear wheel significantly impaired performance, resulting in longer completion times and higher user effort, whereas weight placed at the seat front or backrest had less impact. These findings emphasize the importance of weight distribution on wheelchair mobility and suggest that careful consideration of accessory placement can enhance propulsion efficiency and reduce upper limb biomechanical load. Future research should include experienced wheelchair users to validate these effects in practical settings.